The Rational Factors of Perceived Quality and Perceived Value as the Drivers of Customer Satisfaction and Brand Loyalty - Susanti, Vonny; Sumarwan, Ujang; Simanjuntak, Megawati; Yusuf, Eva Z (UI Scholars Hub, 2020)
This empirical study seeks to investigate which rational factors influence customer satisfaction and brand loyalty stronger. For the purpose of obtaining more accurate findings, the research limits to the common rational factors that influence customer satisfaction to brand loyalty, which is rational perceived quality and rational perceived value. We conduct SEM-PLS (Structural Equation Model-Partial Least Square) to analysis the field data to get the answer of the research question. The finding confirms that buyer’s brand loyalty is driven by customer satisfaction, meanwhile the satisfaction is driven by the rational quality aspects. Furthermore, the service dimensions of reliability and responsiveness are the stronger dimensions of perceived quality than tangible product quality; to conclude that services play a crucial role on the chemical industries. The empirical finding provides a basis for practitioners to manage the brand and the price in such a way as to optimize their profits.